Comparison of total calprotectin levels with S100A8 and S100A9 subunit levels in critically ill patients - Sejersen, Kristina; Mandic Havelka, Aleksandra; Lipcsey, Miklos; Larsson, Anders (SCANDINAVIAN JOURNAL OF CLINICAL & LABORATORY INVESTIGATION, 2025)
Calprotectin is a 24 kD heterodimer of calcium-binding proteins S100A8 and S100A9. At present, there is a lack of knowledge about the specificity of various methods for calprotectin detection, whether they measure only dimers between S100A8 and S100A9, S100A8-S100A8 dimers, S100A9/S100A9 dimers, or free subunits. This study aimed to compare total calprotectin levels with those of its subunits, S100A8 and S100A9, in ICU patients. This prospective observational study includes 271 sepsis and non-sepsis patients. Inclusion criteria were admission to intensive care and the presence or need for an arterial catheter. Plasma total calprotectin was measured at ICU admission and the following two days by particle-enhanced turbidimetric (PETIA) calprotectin reagents from Gentian AS and a Mindray BS380 chemistry analyzer. S100A8 and S100A9 were analyzed by commercial sandwich ELISA DY4570-05, and DY5578, R&D Systems, respectively. Sepsis was defined according to Sepsis-3 as suspected infection and a Sequential organ failure assessment (SOFA) >2 on admission. Receiver operating characteristic (ROC) analysis showed that total calprotectin had a larger area under the curve (AUC) for distinguishing sepsis from non-sepsis patients (0.67) compared to S100A8 (0.59) and S100A9 (0.52). For predicting 30-day mortality, S100A9 had a higher AUC value (0.64) than S100A8 (0.59). However, weak correlations between total calprotectin and its subunits suggest no significant predictive relationship for 30-day mortality, while also highlighting potential assay harmonization challenges across manufacturers.